Farmer demand for clean planting material of biofortified and non-biofortified vegetatively propagated crop varieties: The case of sweetpotato - Mwiti, F.K.; Okello, J.J.; Munei, K.; Low, Jan W. (Elsevier, 2020)
Biofortified orange-fleshed sweetpotato (OFSP), rich in beta carotene, is currently being promoted due to its role in fighting vitamin A deficiency. To promote farmer access to OFSP planting material (i.e., vines) projects establish vine multipliers who are expected to operate commercially. However, most sweetpotato farmers are used to getting vines from social networks free of cost. In this study, we compare farmers’ willingness to pay for clean (i.e., pest and disease free) vines of biofortified and popular non-biofortified sweetpotato varieties. The study thus holds vine “health” constant while assessing the influence of vita- min A biofortification on demand. We then use seemingly unrelated regression technique and data from 481 farmers to assess factors affecting the demand for both types of vines. We find higher willingness to pay for clean non-biofortified sweetpotato vines than bio- fortified sweetpotato vines of similar health, because of the higher nutritional value, good taste, and firmness of the roots of the former. Factors affecting demand for clean vines in- clude the number of children a farmer has, farmer’s age, tastes, preferences, sweetpotato yield and income. These effects differ between biofortified and non-biofortified varieties. We conclude that demand for clean OFSP vines is high, but still lower than for white- fleshed varieties, and discuss implications of the findings.